INFLUENCE OF ANXIETY IN RELATION OF PHYSYICAL ACTIVITY LEVEL AND FOOD CONSUMPTION IN PHYSICAL EDUCATION STUDENTS FROM FEDERAL UNIVERSITY OF PARANA (Fiep Bulletin - online, 2015)
The aim of these study is verify the relationship between the anxiety level, the physical activity level and the food consume in physical education students from Physical education curse from federal university of Paraná.  The sample was constituted of 353 students, males and females, with medium age (sd) of 21,36 (3,07) years old. During the data collect was used Spielberger questionnaire to evaluate the level of anxiety-trace; the level of physical activity was identified through of Habitual physical activity questionnaire and the food consume from a diagnostic. Statistical treatment was descriptive with a linear regression. It's observed that 69,4% of students shows a medium level of anxiety, 38,3% have an active level of physical activity and 33,8% consume more candies and chocolates during a anxiety crisis. There's a significant difference between anxiety and level of physical activity, and food consume. It's concluding that exists an association between the studied variables.
Keywords: .